Merodach-Вaladan II - Brinkman, John A.
I. Introduction; II. M-B, King of the Sealand; III. M-B, King of Babylonia; IV. M-B, Military Strategist; v. Paralipomena: A. The Family of M-B; c. M-B’s Embassy to Hezekiah; c. The Sargonid Letters; D. Sundry Documents; VI. Summary and Conclusion; VII. Bibliography and Ancient Sources.